2022
DOI: 10.1186/s41983-022-00481-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of, and compliance with, self-isolation among COVID-19 patients in South Batinah Governorate, Oman: a cross-sectional study

Abstract: Background Covid-19 pandemic has left deep psychological impacts, especially among infected patients. It is extremely important to understand the extent of those effects, while improving the compliance with isolation measures at the same time. Objectives To detect prevalence of stress using two psychological scales and examine the stress associated factors, also to identify self-isolation compliance rates among COVID-19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[41] One study reported two prevalence estimates. [76] Twenty prevalence estimates were at very high risk of bias, [21, 23, 24, 28, 29, 3137, 40, 47, 6972, 74, 76–78] 14 were at high risk, [21, 22, 27, 38, 4446, 73, 79, 8183, 85] ten had some concerns, [25, 26, 30, 39, 42, 43, 48–68, 80, 84] and one was at low risk. [75] Full details for each study are reported in Supplement S6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] One study reported two prevalence estimates. [76] Twenty prevalence estimates were at very high risk of bias, [21, 23, 24, 28, 29, 3137, 40, 47, 6972, 74, 76–78] 14 were at high risk, [21, 22, 27, 38, 4446, 73, 79, 8183, 85] ten had some concerns, [25, 26, 30, 39, 42, 43, 48–68, 80, 84] and one was at low risk. [75] Full details for each study are reported in Supplement S6.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Twelve studies reported “self-isolate” or “quarantine” (or some such variant), but did not define required behaviours. [25, 33, 34, 42, 43, 47, 74, 75, 79, 80, 8385] There was no mention of a definition of self-isolation in eight studies. [23, 24, 2629, 31, 32]…”
Section: Resultsmentioning
confidence: 99%
“…In a study, Algamdi (2021) found that medication had taken 8.7% and hospitalization 91.3% 30 . In another study, a total of 53% of participants completed the two-week isolation term, with 36.4% experiencing longer periods of isolation 31 .…”
Section: Discussionmentioning
confidence: 98%
“…18 The psychological impact increases as the score rises. According to Creamer et al, the psychological impact of the IES-R score was classified as normal (0-23), mild (24)(25)(26)(27)(28)(29)(30)(31)(32), moderate (33-36), and severe (>37) 19 . The maximal reliability of this tool is excellent, and the three factors have good convergent validity 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study in SBG, in patients diagnosed in the same period, indicated suboptimal compliance with self-isolation measures. 22 …”
Section: Discussionmentioning
confidence: 99%